Unveiling the potential of MSC extracellular vesicles: MiR-122-5p enhancing chondrocyte regeneration in osteoarthritis via autophagy mechanism - Haifeng Zhang; Yanmeng Yang; Yingnan Wu; Vinitha Denslin; Yi Wei Justin Koh; Ling Liu; Wenhai Zhuo; Wing Moon Raymond Lam; Yinxian Yu; James Hoi Po Hui; Zheng Yang (Stem Cell Research & Therapy)
Abstract Background Osteoarthritis (OA) is one of the most prevalent degenerative joint diseases, while the mechanism by which extracellular vesicles (EVs) promote chondrocyte regeneration remains unclear. The study assessed the effect of hypoxic mesenchymal stem cells (MSCs)-derived EVs on cartilage repair in a rat OA model. Methods The effects of EVs on chondrocyte regeneration and autophagy were evaluated in vitro. The influence of specific micro RNA (miRNA) and downstream target genes was examined following EV miRNA sequencing and multiple intersecting database analysis. Results We found EVs derived from hypoxia preconditioned human MSCs to promote cartilage repair in rat OA and enhance the proliferation and migration of chondrocytes in vitro, mediated via chondrocyte autophagy. MiRNA sequencing revealed a significant enrichment of miRNA122-5p in hypoxic MSCs EV, which through regulation of the target gene, DUSP2, mediated autophagy and participated in chondrocyte regeneration. DUSP2 regulation of chondrocyte autophagy could act via the phosphorylation of ERK1/2 and P38. Conclusions This study demonstrates that EVs released by MSCs under hypoxic conditions have a beneficial effect on chondrocyte regeneration. A novel mechanism for chondrocyte autophagy is mediated by miR122-5P and DUSP2 target molecules, providing new insights into OA treatments.